Wide-band fanned-out supercontinuum source covering O-, E-,S-,C-,L-and U-bands - Ahmad, Harith; Abdul Latif, Amirah; Awang, Noor Azura; Zulkifli, Mohd Zamani; Thambiratnam, Kavintheran; A. Ghani, Zawajer; Harun, Sulaiman Wadi (Elsevier, 2012)
A wide-band supercontinuum source generated by mode-locked pulses injected into a Highly Non-Linear Fiber (HNLF) is proposed and demonstrated. A 49 cm long Bismuth–Erbium Doped Fiber (Bi–EDF) pumped by two 1480 nm laser diodes acts as the active gain medium for a ring fiber laser, from which mode-locked pulses are obtained using the Non-Polarization Rotation (NPR) technique. The mode-locked pulses are then injected into a 100 m long HLNF with a dispersion of 0.15 ps/nm km at 1550 nm to generate a supercontinuum spectrum spanning from 1340 nm to more than 1680 nm with a pulse width of 0.08 ps and an average power of 17 dBm. The supercontinuum spectrum is sliced using a 24 channel Arrayed Waveguide Grating (AWG) with a channel spacing of 100 GHz to obtain a fanned-out laser output covering the O-, E-, S-, C-, L- and U-bands. The lasing wavelengths obtained have an average pulse width of 9 ps with only minor fluctuations and a mode-locked repetition rate of 40 MHz, and is sufficiently stable to be used in a variety of sensing and communication applications, most notably as cost-effective sources for Fiber-to-the-Home (FTTH) networks